Field notes contributed by Rob Thelen, spring 1996 - Thelen, Robet al (1996)
Spring report of birds and locations contributed by Rob Thelen. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1996. Epson - sheet feed/flatbed